CREATION OF ALGORITHMS FOR CALCULATING COEFFICIENTS IN PARTIAL POLYNOMIAL BASES OF KHAAR - Abdirayimov, Tojinur Normo‘min o‘g‘li (INTERNATIONAL CONFERENCES, 2022)
In this article, parallel algorithms have been developed for digital signal processing on piecewise-polynomial basis of Haar which is based on Analog Devices’ Blackfin ADSP-BF561 dual-core processors. Based on these algorithms, developing of dual-core parallel computing program on VisualDSP++ has been considered. Functional descriptions of the Blackfin ADSPBF561 dual-core processor architecture are given. The architecture and components of the processor core have been described.